2002
DOI: 10.1080/02791072.2002.10399977
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Scene Roles and HIV Risk Among Puerto Rican Injection Drug Users in East Harlem, New York and Bayamón, Puerto Rico

Abstract: This article describes and compares distributions of drug-scene roles, frequency of engaging in role behaviors, and relationships of role-holding to high-risk behaviors and sexual partnerships among Puerto Rican injection drug users in New York and Puerto Rico. For this study 561 street-recruited injection drug users in East Harlem, New York, and 312 in Bayamón, Puerto Rico were asked the number of days (in the last 30) in which they earned money or drugs in each of seven drug-scene roles; and about behaviors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…While caution is warranted in the interpretation of univariate results, these data may suggest that the initiation of crystal methamphetamine by youth residing in the DTS signals an immersion into a street-based illicit drug scene, and may therefore represent a potential interventional point for the prevention of street entrenchment among youth. Taken alongside the findings of our multivariate analysis and previous qualitative work from our study setting, these results suggest that the DTS may be an introductory area for those youth drawn towards street-involvement and may uniquely facilitate transitions to the development of more intense risk behaviors as observed among youth in the DTES (21). This phenomenon may also be a product of the socio-historical context of drug use, illicit drug culture, and policy responses in the city of Vancouver.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…While caution is warranted in the interpretation of univariate results, these data may suggest that the initiation of crystal methamphetamine by youth residing in the DTS signals an immersion into a street-based illicit drug scene, and may therefore represent a potential interventional point for the prevention of street entrenchment among youth. Taken alongside the findings of our multivariate analysis and previous qualitative work from our study setting, these results suggest that the DTS may be an introductory area for those youth drawn towards street-involvement and may uniquely facilitate transitions to the development of more intense risk behaviors as observed among youth in the DTES (21). This phenomenon may also be a product of the socio-historical context of drug use, illicit drug culture, and policy responses in the city of Vancouver.…”
Section: Discussionsupporting
confidence: 75%
“…That we observed non-significant risks for a variety of types of drug use as well as for involvement in drug dealing and the sex trade between street youth residing in the DTS and the DTES may suggest that interventions to reduce youth entrenchment in an open-air illicit drug market should take into consideration the role of adjacent neighborhood street scenes in influencing drug use patterns (21). Specifically, while we found that participants residing in the DTES were more likely than those in the DTS to report having a primary illicit income source, we found no significant differences in risk of drug dealing, as well as comparably high levels of this illicit activity, among individuals residing in both neighborhoods.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…3, 5-10 Other studies have also focused specifically on Puerto Ricans. 7,[11][12] In general, these studies have demonstrated that an individual's perception of risk rather than actual risk such as IDU and non-IDU determine HIV infectionrelated behavior including unsafe sex. Therefore, a comprehensive and reliable methodology to assess risk perception among minority populations is necessary in reducing HIV incidence and prevalence.…”
Section: Introductionmentioning
confidence: 99%